Distribution-led growth in the long run - Michalis Nikiforos (Levy Economics Institute of Bard College, 2014)
The paper examines the long-run fluctuations in growth and distribution through the prism of wage-and profit-led growth. We argue that the relation between distribution of income and growth changes over time. We propose an endogenous mechanism that leads to fluctuations between wage- and profit-led periods. Our model is a linear version of Goodwin's predator-prey model, but with a reversal of the roles for predator and prey: the growth rate acts as the predator and the distribution of income as the prey. These fluctuations need to be taken into account when someone estimates empirically the effect of a change in distribution on utilization and growth. We also examine our argument in relation to the double movement of Karl Polanyi, the Kuznets curve, and the theories of long swings proposed by Albert Hirschman and Michal Kalecki.
Keywords: B22; E11; E12; E21; E22; E32; 330; Distribution-led; Long Swings; Oscillations; Predator-prey